2019
DOI: 10.1038/s41598-019-46849-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Kidney Dysfunction from Polypharmacy among Older Patients: A Nested Case-Control Study of the South Korean Senior Cohort

Abstract: Polypharmacy, the concurrent use of multiple medicines, could increase the risk of kidney dysfunction among older adults because it likely burdens the aging kidneys to excrete multiple pharmaceutical ingredients and their metabolites. This study aimed to examine the relation between polypharmacy and kidney dysfunction among older patients. A nested case-control study was conducted using the National Health Insurance Service – Senior Cohort (NHIS-SC, 2009–2013), representative of the Korean senior population. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 101 publications
5
9
0
3
Order By: Relevance
“…Hyperkalemia occurs most readily when there is renal dysfunction because kidneys play an important role in potassium homeostasis, where 90% of the excess potassium is excreted specifically through the kidneys [16]. The results of this study adhere to the above theory, since, according to our observations, the factors associated with abnormal renal function [17], among the various possible factors, showed the most significant impact on the development of ACEIor ARB-induced hyperkalemia [18]. That is, the incidence of hyperkalemia was higher in the presence of higher creatinine, lower MDRD-eGFR, and comorbid renal failure.…”
Section: Discussionsupporting
confidence: 83%
“…Hyperkalemia occurs most readily when there is renal dysfunction because kidneys play an important role in potassium homeostasis, where 90% of the excess potassium is excreted specifically through the kidneys [16]. The results of this study adhere to the above theory, since, according to our observations, the factors associated with abnormal renal function [17], among the various possible factors, showed the most significant impact on the development of ACEIor ARB-induced hyperkalemia [18]. That is, the incidence of hyperkalemia was higher in the presence of higher creatinine, lower MDRD-eGFR, and comorbid renal failure.…”
Section: Discussionsupporting
confidence: 83%
“…42 The concurrent use of multiple medications increased the risk of kidney dysfunction among older adults because it could burden the ageing kidneys to excrete multiple pharmaceutical ingredients and their metabolites. 43 The results of other relevant studies on the impact of polypharmacy on kidney function also indicated that every additional drug prescribed among older adults will have an independent and immediate harmful impact on their kidney function. 44 These findings suggest that some patients with chronic diseases did not have enough knowledge about drug use.…”
Section: Open Accessmentioning
confidence: 99%
“…However, not only the elderly are at risk; adults with chronic diseases, such as cancer [33], chronic obstructive pulmonary disease [34], and diabetes [35] are in danger as a result of polypharmacy; patients with CKD, a disease commonly associated with the premature aging [36], are at particular risk [17-19]. Although polypharmacy has a significant potential to deteriorate kidney function [22, 37], there have been no studies that explore the hazard of polypharmacy on the progression of CKD in the CKD population. In this large-scaled prospective predialysis CKD cohort, however, we could not confirm the direct effect of multiple medications on the CKD progression.…”
Section: Discussionmentioning
confidence: 99%